A 30,000-km journey by Apus apus pekinensis tracks arid lands between northern China and south-western Africa ... - Zhao, Yanyan; Zhao, Xinru; Wu, Lan; Mu, Tong; Yu, Fang; Kearsley, Lyndon; Liang, Xuan; Fu, Jianping; Hou, Xiaoru; Peng, Peng; Li, Xiaoyang; Zhang, Tao; et al. (figshare, 2022)
Abstract Background As a widely distributed and aerial migratory bird, the Common Swift (Apus apus) flies over a wide geographic range in Eurasia and Africa during migration. Although some studies have revealed the migration routes and phenology of European populations, A. a. apus (from hereon the nominate apus), the route used by its East Asian counterpart A. a. pekinensis (from hereon pekinensis) remained a mystery. Methods Using light level geolocators, we studied the migration of adult pekinensis breeding in Beijing from 2014 to 2018, and analysed full annual tracks obtained from 25 individuals. In addition, we used the mean monthly precipitation to assess the seasonal variations in humidity for the distribution ranges of the nominate apus and pekinensis. This environmental variable is considered to be critically relevant to their migratory phenology and food resource abundance. Results Our results show that the swifts perform a round-trip journey of ca 30,000 km each year, representing a detour of 26% ...